Saccostrea Dollfus & Dautzenberg 1920 ... - Wells, Fred E.; Lukehurst, Sherralee S.; Fullwood, Laura A. F.; Harvey, Euan S. (Zenodo, 2024)
Saccostrea lineage A (Figures 2a, c, 3; Table 1) Brief description of shell: Often densely packed so shells grow to fit available space. Medium size, oval, length 5 cm or less, hinge to tip of shell. Margins crenulated, margins may have short lobes that can be worn off. Outer surface off white. Inner white, adductor scar on left valve purple. Oysters grown individually for aquaculture up to 6 cm, elongate, left valve deeper. Records in the present survey: Ashburton Port area: East end Thevenard Island; Hooley Creek; Salt Creek; Beadon Creek jetty; Four Mile Creek. Dampier Port area: Withnell Bay, Burrup Peninsula; Southern entrance to King Bay; Eastern King Bay; Dampier boat landing; Watering Cove, Burrup Peninsula; Karratha Bay, West Lewis Island; North side of East Intercourse Island. Port Samson port area: Point Samson. Port Hedland Port area: Public boat ramp, Port Hedland reef, Pretty Pool. Previous records in the Pilbara verified by DNA sequences: Lam and Morton (2006): Exmouth; Barrow Island; Watering ... : Published as part of Wells, Fred E., Lukehurst, Sherralee S., Fullwood, Laura A. F. & Harvey, Euan S., 2024, Distribution of intertidal rock oysters in the Pilbara, Western Australia, pp. 131-143 in Management of Biological Invasions 15 (1) on page 137, DOI: 10.3391/mbi.2024.15.1.08, http://zenodo.org/record/12628087 ...